The metanarrative hall of mirrors reflex action in fiction and film - Stewart, Garrett (Bloomsbury Academic, 2022)
"A profound and entertaining new work on contemporary narrative in film and literature from celebrated literary critic, Garrett Stewart"--Provided by publisher.